Deaths at sea in the Pacific Islands: Challenges and opportunities for civil registration and vital statistics systems - Carah Figueroa; Gloria Mathenge; Christine Linhart; Philip A.S. James (Asia-Pacific Sustainable Development Journal, 2020)
Accurate and reliable death statistics produced by civil registration and vital statistics systems are essential for health planning and programme evaluation. The quality of death registration data in Pacific island countries and territories remains suboptimal. Data on deaths occurring at sea are especially limited. While coastal and oceanic activities are the norm and essential to the livelihoods of Pacific island populations, such activities pose risks for accidents at sea, especially those involving small-scale vessels. In this paper, the scale of deaths at sea associated with small vessels in three Pacific island countries or territories over the period 2008-2017 is investigated using data from the health, civil registry, and police and fisheries departments, and reports produced by national statistics offices, ministries of health, the Pacific Community, the World Health Organization and media sources. Data on deaths at sea were found to be fragmented among multiple sources and missing key information on age, sex, and cause. Standardized procedures for reporting deaths and accidents at sea and harmonized data sharing between local communities and government agencies are urgently needed to improve civil registration and vital statistics systems and sea safety in the Pacific island subregion.